Analysis of the Induction Program During Employee Recruitment and Selection at Pt. Globalindo Intimates - Amalia Lutfi Septinawati; Jaya Addin Linando (Faculty of Economics and Muamalat, Universiti Sains Islam Malaysia, 2025)
Islamic Banking, Accounting & Finance International Conference 2024 (iBAF 2024) Theme: "Revolutionizing Islamic Finance, Accounting and Banking Through Artificial Intelligence (AI)" 12-13 November 2024 Editors: Dr. Amalina Mursidi, Dr Suhaila Abdul Hamid, Prof Madya Dr. Norhaziah Nawai, Prof Madya Dr. Muhamad Azrin Nazri,Dr. Mohd Adha Ibrahim